John Sayles - Shumway, David R. (Contemporary film directors., 2012)
John Sayles is the very paradigm of the contemporary independent filmmaker. By raising much of the funding for his films himself, Sayles functions more independently than most directors. In this study, Shumway examines the defining characteristic of Sayles's cinema: its realism.